2020
DOI: 10.1038/s41598-020-65156-0
|View full text |Cite|
|
Sign up to set email alerts
|

The endocast of the Night Parrot (Pezoporus occidentalis) reveals insights into its sensory ecology and the evolution of nocturnality in birds

Abstract: The Night Parrot (Pezoporus occidentalis) is a rare, nocturnal parrot species that has largely escaped scientific investigation due to its behaviour and habitat preferences. Recent field studies have revealed some insights into Night Parrot behaviour, but nothing is known of its sensory abilities. Here, we used μCT scans of an intact Night Parrot specimen to determine if its visual system shares similarities with other nocturnal species. The endocast of the Night Parrot revealed relatively small optic lobes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…Endocranial shape has been extensively used as a proxy for the brain shape, to compare or infer the ecology of both extant and extinct species (for a review, see Balanoff and Bever, 2017); including habitat (Allemand et al 2017), sensory abilities (Lautenschlager et al 2012;Holloway et al 2013;Carril et al 2016) and behavior (Balanoff et al 2016;Bertrand et al 2019;Macrì et al 2019). However, endocranial morphology could also be used to make more precise inferences regarding the sensory ecology of elusive (Iwaniuk et al 2020) or fossil species, if we were able to recognize a direct link between sensory-relevant aspects of the ecology of extant species and the shape of their endocranium. An extensive comparative study of the brain shape of fish has demonstrated a relationship between brain shape and precise details of the ecology such as microhabitat use and diet (Kotrschal et al 1998) supporting the hypothesis that brain shape is adaptive.…”
Section: Introductionmentioning
confidence: 99%
“…Endocranial shape has been extensively used as a proxy for the brain shape, to compare or infer the ecology of both extant and extinct species (for a review, see Balanoff and Bever, 2017); including habitat (Allemand et al 2017), sensory abilities (Lautenschlager et al 2012;Holloway et al 2013;Carril et al 2016) and behavior (Balanoff et al 2016;Bertrand et al 2019;Macrì et al 2019). However, endocranial morphology could also be used to make more precise inferences regarding the sensory ecology of elusive (Iwaniuk et al 2020) or fossil species, if we were able to recognize a direct link between sensory-relevant aspects of the ecology of extant species and the shape of their endocranium. An extensive comparative study of the brain shape of fish has demonstrated a relationship between brain shape and precise details of the ecology such as microhabitat use and diet (Kotrschal et al 1998) supporting the hypothesis that brain shape is adaptive.…”
Section: Introductionmentioning
confidence: 99%
“…Optic lobe structures in dromornithids are somewhat hypotrophied in comparison to those of the extant galloanseres. Iwaniuk et al [166] showed that the optic lobe of the nocturnal Night parrot (Pezoporus occidentalis) was relatively reduced compared with those of diurnal parrots, but orbit size did not differ between them. As noted above (see Section 4.4.2.1), eye shape, corneal diameter and retinal topography are better predictors low-light sensitivity than eye size alone (e.g., [86,141,142]).…”
Section: Optic Lobementioning
confidence: 99%
“…Brains have yet to be examined of the night parrot, but it too shows evidence of higher sensitivity and lower acuity compared to similarly sized diurnal parrots [17]. This has implications for conservation efforts, as fences and powerlines may pose greater threats to the night parrot than their diurnal relatives [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although retinal summation is best determined from microscopic examination of the retina, it can be estimated in birds by comparing the orbit diameter (reflective of retinal area) with the diameter of the optic foramen (reflective of the number of retinal ganglion cells) [ 16 ]. Thus, nocturnal species tend to have small optic foramina relative to orbit diameters [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation